1999
DOI: 10.1177/009286159903300332
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Understanding Patient Attribution of Adverse Drug Reaction Symptoms

Abstract: The study uddressed issues surrounding the pntient j . recognition of whether a symptom is d r u g or niseiise-related. Studies have demonstrated that the infornmtion the Iaypopulation has about illness can be organized into Jive categories: identity (symptoms and label), cause. time course. consequences. and cure. These elements, termed illness representations or prototyes. facilitate patient interpretation and response to symptoms as they occur the ore tic ally^ patients may have such a framework f o r inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Studies in both the UK and the US have proposed that patients could identify their ADRs related to the suspected medicines based on both timing issues and their own knowledge [18][19]. Our study also confirmed this, with some being aware of individual drugs' potential for causing ADRs, However beliefs about medicines also influenced some individuals' views on the association.…”
Section: Main Findingssupporting
confidence: 81%
“…Studies in both the UK and the US have proposed that patients could identify their ADRs related to the suspected medicines based on both timing issues and their own knowledge [18][19]. Our study also confirmed this, with some being aware of individual drugs' potential for causing ADRs, However beliefs about medicines also influenced some individuals' views on the association.…”
Section: Main Findingssupporting
confidence: 81%
“…A qualitative study in the USA explored the processes used by patients to decide possible causes of symptoms and potential attribution as a suspected ADR. The results indicated that ‘people have knowledge about ADR symptoms that is substantially accurate’ and that they may use a ‘prototype’ to facilitate identification of symptoms as an adverse effect [23].…”
Section: Resultsmentioning
confidence: 99%
“…Relevant known attributes of ADEs were duration, frequency, severity, and seriousness of the ADE; its impact on activities; and the patient's benefit-risk assessment of the drug [24,[30][31][32]. Existing questionnaires were screened for questions covering these topics [26,27,[33][34][35].…”
Section: Assessing Nature and Causality Of Adesmentioning
confidence: 99%